Knowledge of home gardening and anthropometric status of adult women in Odeda Local Government, Abeokuta, Ogun State, Nigeria - ILO, Jumoke Georgina; Onabanjo, Oluseye Olusegun; Hamzat, Aderayo Maryam (International Journal on Food, Agriculture and Natural Resources, 2023)
A healthy lifestyle and illness prevention depend on adequate nutrition, and homestead food production, including home gardening, is one way to increase access and lower the cost of healthy foods. This study was carried out in Odeda Local Government Area of Ogun State to assess the anthropometric indices and knowledge of home gardening of women. The sample size comprised of 170 respondents which were chosen using a multistage sampling technique. Data on sociodemographic, socioeconomic variables, and home gardening knowledge were obtained using an interviewer-administered, well-structured questionnaire. Anthropometric measurements were taken using standard procedures. The nutritional status was assessed using anthropometric measurements.  Version 20.0 of Statistical Product and Service Solutions (SPSS) was used to analyze the data. The findings were presented as frequency, percentage, mean, and standard deviation. The threshold for statistical significance was set at p 0.05. The responders were 33.5 years old on average. The majority of respondents (85.3%) had at least a primary education.  It was found that 94.7% of the adult women had good knowledge of home gardening, 4.7% had average knowledge, and 0.6% had low knowledge. The nutritional status of the respondents showed that 24.1 percent were overweight, 10.6 percent were underweight, and 10.6 percent were obese. The home garden knowledge score and the anthropometric measurement (BMI) were shown to be significantly associated. The result of this study is an indication that women who are knowledgeable about gardening at home are more likely to have higher nutritional status.